Adult patient and/or carer experiences of planning for hospital discharge after major trauma: a qualitative systematic review protocol. Issue 2 (20th February 2020) - Collins, Jeanette; Lizarondo, Lucylynn; Porritt, Kylie
ABSTRACT: Objective: To investigate patient and/or carer experiences of planning for discharge from an acute setting after a major trauma event. Introduction: The experience of injury through major trauma is a worldwide issue that affects people of any age. These patients often experience long-lasting disability. During discharge from the acute setting, patients are at a high risk of experiencing an adverse event due to the complex nature of the process. This review aims to explore patient/carer opinion of their encounter with the discharge planning process following major trauma. Inclusion criteria: This review will consider studies that include patients aged between 18 and 65 who had major traumatic central nervous system injury or were allocated an Injury Severity Score >12, with demonstrated possibility of having an ongoing disability at least one year post-injury. Qualitative studies exploring patient and/or carer experiences of their participation in discharge planning from a trauma unit, acute ward or inpatient rehabilitation to a community setting will be included. Methods: A three-stage search will be conducted and will include unpublished and gray literature. Databases to be searched include PubMed, Embase, PyscInfo, Scopus and CINAHL. Only studies published in English will be considered. Identified studies will be screened for inclusion in the review by two independent reviewers. Data will be extracted using a standardized tool and reviewers will discuss any disagreement. Data synthesis will adhere to the meta-aggregative approach to categorize findings. The categories will be synthesized into a set of findings that can be applied as evidence-based practice. Systematic review registration number: PROSPERO CRD42019138431.